2015 International Conference on Electrical and Information Technologies (ICEIT) 2015
DOI: 10.1109/eitech.2015.7162979
|View full text |Cite
|
Sign up to set email alerts
|

A review of feature extraction techniques for handwritten Arabic text recognition

Abstract: Research in Arabic handwritten recognition has been of growing interest in the last few decades. This is mainly due to its broad spectrum of applications in different fields such as bank check processing, form data entry, postal mail sorting, automatic processing of old manuscripts, etc. In the literature, numerous techniques have been proposed for feature extraction and applied to various types of images. This work provides a comprehensive review of these methods for off-line handwritten Arabic text recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…The performance evaluation outcomes spotlight reliability of the combination of the SVM and Ridgelet tools for recognition of the handwritten Arabic words. EI Qacimy et al [11] suggested offline, word-based system for recognition of the handwritten Arabic text depending on the DCT features and a SVM classifier that is improved by reject option. This system comprised four key processes, namely, preprocessing, segmentation into sub-words, extraction based on DCT features, and classification by the SVM RBF classifier.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance evaluation outcomes spotlight reliability of the combination of the SVM and Ridgelet tools for recognition of the handwritten Arabic words. EI Qacimy et al [11] suggested offline, word-based system for recognition of the handwritten Arabic text depending on the DCT features and a SVM classifier that is improved by reject option. This system comprised four key processes, namely, preprocessing, segmentation into sub-words, extraction based on DCT features, and classification by the SVM RBF classifier.…”
Section: Related Workmentioning
confidence: 99%
“…However, it may be generalized easily to the multi-class classification problems. The fundamental form of the linear SVM classifier attempts to discovery the optimum hyperplane that separate the best set of samples that belong to differing classes [11]. www.ijacsa.thesai.org…”
Section: E Classification Using Svm Classifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…El Qacimy et al in (El Qacimy, Hammouch & Kerroum, 2015), provided a brief review for the feature extraction methods to the offline handwritten Arabic text recognition in addition to presenting both description for the used database and the recognition rate in the proposed approaches in this study. However, it will be such a quite profit to the research discussion and methodology because it includes a fully discussion for the methods of feature extraction that will help in the contour extraction section in our research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…El Qacimy et al (2015), provided a brief review for the feature extraction methods to the offline handwritten Arabic text recognition in addition to presenting both description for the used database and the recognition rate in the proposed approaches in this study. However, it will be such a quite profit to the research discussion and methodology because it includes a fully discussion for the methods of feature extraction that will help in the contour extraction section in our research.…”
Section: Kofimentioning
confidence: 99%